Sistem Pakar Untuk Mendiagnosa Penyakit Lupus dengan Metode Forward Chaining Menggunakan Web - Indah Wahyuni Bugis; Jhonson Efendi Hutagalung; Indra Ramadona Harahap (Building of Informatics, Technology and Science (BITS), 2022)
Lupus disease can attack humans quickly. The initial symptoms that will arise are the same as common diseases such as high fever, prolonged thrush, and also hair will fall out and start to run out one by one until it will go bald, the form of red rashes that appear on the skin, excessive joint pain in the body, easily tired, weight loss, causing paralysis, there are many other symptoms. The lack of availability of a doctor and the limited knowledge of people in remote areas often make the initial diagnosis of the disease late, therefore the application of an expert system is considered very useful to help diagnose lupus early in view of the time and energy of an expert doctor. In the health sector there is an artificial intelligence called an expert system, which is a computer system that uses knowledge, facts and reasoning techniques in solving problems that can usually only be solved by an expert in their field. This study uses an expert system application method in making decisions using a forward chaining inference engine where the goal driven data will start a search on the initial node to the goal node until it gets results. From the diagnostic process, the system provides a selection of the symptoms experienced by the patient, resulting in CLE type lupus (Cutaneus Lupus Erythematosus)